RIBA DAN BUNGA BANK DALAM PERSPEKTIF TEORI NASAKH MAHMUD MUHAMMAD THAHA - Wartoyo Wartoyo (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThe purpose of this article is to conduct a study of the verses of usury in the Qur'an using Mahmoud Muhammad Thaha's nasakh theory, then proceed with an analysis of the application of the nasakh theory to bank interest, which so far there are still many disagreements among Muslim scholars regarding the law, whether it includes usury or not usury. The method used in writing this article is to use qualitative methods with analytic descriptive analysis with the main data source coming from library data (library research). The results of this study found that the practice of riba regardless of its type, form, quality, and quantity is prohibited. Because usury is contrary to the spirit of justice in the distribution of income and assets of Muslims. The prohibition of usury has the same position as the prohibition of other forms of a prohibition against other practices that can damage the order of life in society, such as the prohibition of drinking and adultery, which according to the view of all scholars are (mani'ah jami). 'ah) thorough and universal.Keywords: Nasakh theory; Riba; Bank interest; Makkiyah; Madaniyah.